Providing comprehensive nurse-led health education to health failure patients in order to enhancing their self-management - Kristinawati, Beti; Sukma, Nori; Wijayanti, Nove Wiand Dwi; Mardana, Nyofan Wahyu (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2025)
Introduction: Heart failure patients' lack of awareness and inactivity regarding disease recognition and self-management. The study aimed to determine the advantages of instituting education administered by nurses capable of self-managing heart failure patients.Methods: During the preparation phase, a preliminary study was conducted by conducting interviews, making observations, and securing permission for community service at UNS Hospital. The final stage, evaluation, involves measuring the effectiveness of this service by determining how well patients with heart failure comprehend educational material by administering a test.Results: These findings indicate that training and education can result in a 32% increase in the self-management knowledge of heart failure patients.Conclusion: Patients will have a greater understanding of self-management due to the provided education, thereby decreasing the severity of the disease and the likelihood of readmission.